Problematika Pemanfaatan Media Pembelajaran Berbasis TIK pada Guru Matematika - Nur Rohmah Yulia Ningrum; Maria Natalia Paschalina Awi (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The development of Information and Communication Technology has had a major impact on the education sector. Various abilities should be utilized in the world of education in order to create a better education system, in terms of infrastructure, increasing the professionalism of the quality of human resources educators (teachers) and producing quality students.The purpose of this study was to determine the problems faced by teachers in the use of technology-based learning media in learning mathematics. This type of research is descriptive qualitative, the subjects in this study are mathematics teachers from elementary to middle school levels with a total of 35 teachers from various regions. The instruments used in this study were questionnaires and interviews. Interviews were conducted to reconfirm the unclear answers to the questionnaire from each subject. Based on the results of data analysis, it can be concluded that teachers with teaching time of 2-5 years are more active and creative in using methods and media in learning, in contrast to the case with teachers with teaching time of more than 10 years tend to prefer to use conventional methods because of habits and more comfortable with this method